Threads of suspicion - Henderson, Dee (Henderson, Dee. Evie Blackwell cold case., 2017)
Pressured to deliver results through the governor's new Missing Persons Task Force, Detective Evie Blackwell and her new partner, David, investigate two cold cases while navigating growing suspicions about public agendas and questions in Evie's personal life.